Treatment Options for Advanced Non-Small Cell Lung Cancer After Failure of Previous Immune Checkpoint Inhibitors and Chemotherapy: Meta-Analysis of Five Randomized Controlled Trials - Andrea Messori; Andrea Ossato; Lorenzo Gasperoni; Luna Del Bono; Alessandro Inno; Vera Damuzzo (Current Oncology)
Background: Immune checkpoint inhibitors (ICIs), either alone or in combination with platinum-based chemotherapy, are effective in the first-line treatment of metastatic, non-oncogene-addicted, non-small cell lung cancer (NSCLC). However, when NSCLC patients progress, the efficacy of available treatment options is limited. Methods: We undertook a meta-analysis that compared combination regimens with the current standard of care. Only randomized controlled trials (RCTs) were included (endpoint, overall survival [OS]). Our analysis used an artificial intelligence software program that reconstructs individual patient data from Kaplan–Meier curves. Hazard ratio (HR) with 95% confidence interval (CI) was the main parameter. Heterogeneity was based on Wald’s test and likelihood ratio test. Results: Five RCTs were included, whose experimental arms included five different combinations. In our analysis, these combination regimes showed no OS benefit compared to chemotherapy (HR = 1.066, 95%CI, 0.9311 to 1.221; p = 0.35). Among the five control arms, cross-trial heterogeneity was remarkably low (likelihood ratio test = 3.76 on 4 df, p = 0.40; Wald test = 3.83 on 4 df, p = 0.40. Discussion: In conclusion, five new second-line combination treatments for patients with NSCLC were not found to determine any benefit in terms of OS in comparison with the current standard of care.